" Employment of Mathematical Modelling for the Study of Main Indicators of Water Quality in the Reservoirs of some Surface Dams in the Syrian Costal Region " - صبوح حسام; جعفر رائد; القرحيلي ريم (Latakia University Journal -Engineering Sciences Series, 2021)
The research can be summarised as an empirical and analytical examination using mathematical modeling to study and evaluate the main indicators of water quality in the reservoirs of three small surface dams in the governorate of Lattakia, namely, Al-Qanjra Dam Reservoir, Kersana Dam Reservoir and Khirbet al-Jawziya Dam Reservoir, over the period of an entire year (2019). The research also includes a field and laboratory study which includes identifying each of the following parameters: dissolved oxygen, biochemical need of oxygen, dam water temperature, nitrates, phosphorus and pH. For the processing and analysis of the laboratory measurement results, the (LAKE2K) mathematical model is employed, which allows to select the most important indicators to assess the water quality in the water sources in general, being in this research as follows: concentration of Dissolved Oxygen (DO), concentration of Nitrates ions (NO3) and concentration of Phosphorus ions (Porg). Field and laboratory study shows that the concentration of dissolved oxygen does not decrease below level (5 mg/l) in all months of the year for the Reservoirs of Kersana and Khirbet al-Jawziya. In Al-Qanjra Reservoir, the measurements show lower values for this indicator in the months of July and August. Concentration of Nitrates ions does not exceed the (50 mg/l) value; correspondingly, concentration of phosphorus ions does not exceed the (0.5 mg/l) level in all months of the year for the three studied lakes. The research results allow to set a vision and an assessment of the water quality in the three Reservoirs, as they are in mediocre (Al-Qanjra Dam Reservoir) to a good (Kersana Dam Reservoir and Khirbet al-Jawziya Dam Reservoir) state. To conclude, we have demonstrated the findings that we have come up with after reading the laboratory measurements and analysing the results given by the employed mathematical model. Through that we have presented a set of recommendations that are most necessary to carry out in order to protect the water in the three studied Reservoirs from pollution that comes to them from various sources.